The Influence of Social Media Marketing and Egoistic Motivation on Purchase Intention through Green Attitude as A Moderating Variable in Organic Beverage Consumers - Hariyanto, Dhito Rofiadhi Ilhamsyah; Sugandhini, Dyah (Southeast Asian Business Review, 2024)
This research discusses the influence of social media marketing and egoistic motivation on purchase intention through green attitude as a moderating variable in organic beverage consumers. Data for this research were collected using a quantitative approach with a questionnaire method. The data used were primary data from the responses of 200 organic beverage consumers in the Special Region of Yogyakarta selected through purposive sampling. Data collection was measured using a Likert scale and then analyzed using PLS in SMART PLS 3.0 software. The results of the study indicate that 1) Social Media Marketing directly and significant influence on Purchase Intention, 2) Egoistic Motivation directly and significant influence on Purchase Intention, 3) Green Attitude directly and significant influence on Purchase Intention, 4) Green Attitude can act as a moderating variable in the positive and significant influence of Social Media Marketing on Purchase Intention, 5) Green Attitude can act as a moderating variable in the positive and significant influence of Egoistic Motivation on Purchase Intention.